2020
DOI: 10.1140/epje/i2020-11933-4
|View full text |Cite
|
Sign up to set email alerts
|

Lubricated sliding friction: Role of interfacial fluid slip and surface roughness

Abstract: We derive approximate mean field equations for the fluid flow between elastic solids with randomly rough surfaces including interfacial fluid slip and shear thinning. We present numerical results for the fluid flow and friction factors for realistic systems, in particular, we consider the case of an elastic cylinder with random surface roughness in relative sliding contact with a flat rigid (low-energy) countersurface. We present experimental data for the sliding friction between rubber stoppers and glass barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
8
2
Order By: Relevance
“…On the silanized surface the contamination film binds weaker than on the clean surface but, nevertheless, it appear that in many cases there is negligible slip between the contamination film and the silanized glass surface. This differ from the result of a recent study where slip was observed between a rubber stopper and a glass barrel with baked-on silicone oil (Rotella et al, 2020). In wet conditions the silanazed glass surface result in a higher maximum friction coefficient than the hydrophilic glass surface.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the silanized surface the contamination film binds weaker than on the clean surface but, nevertheless, it appear that in many cases there is negligible slip between the contamination film and the silanized glass surface. This differ from the result of a recent study where slip was observed between a rubber stopper and a glass barrel with baked-on silicone oil (Rotella et al, 2020). In wet conditions the silanazed glass surface result in a higher maximum friction coefficient than the hydrophilic glass surface.…”
Section: Discussioncontrasting
confidence: 99%
“…For a silanized glass surface (see Figure 2C) some of the slip may be localized to the interface between the hydrophobic coating and the contamination film (Rotella et al, 2020), but the experimental results presented below indicate that the main slip again occur either within the contamination film or at the interface between the rubber and the contamination film. We will show below that the contamination film may be derived mainly from the rubber rather than from other origins.…”
Section: Rubber Friction: Qualitative Discussionmentioning
confidence: 83%
“…However, the study in Ref. [12] indicates that even for very inert substrate the main slip may occur either within the contamination film or at the interface between the rubber and the contamination film.…”
Section: Theory: Frictionmentioning
confidence: 99%
“…Fluid flow at the interface between elastic solids is a complicated topic, in general involving elastic deformations, complex fluid rheology and interfacial fluid slip [1]. In particular, the influence of the surface roughness on the fluid flow dynamics is a highly complex topic.…”
Section: Introductionmentioning
confidence: 99%
“…These factors depend on the average surface separationū, which will vary throughout the nominal contact region;ū is the local interfacial surface separation u(x, y) averaged over the surface roughness [2,3]. In several publications it has been shown how to calculate the fluid flow factors, which enter in the (modified) Reynolds equation, and the friction factors, which enter in the expression for the shear stress acting on the solids [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%